Influence of Corneal Topographic Parameters in the Decentration of Orthokeratology. Issue 6 (November 2019) - Gu, Tianpu; Gong, Boteng; Lu, Daqian; Lin, Weiping; Li, Na; He, Qing; Wei, Ruihua
Abstract : Objective: To investigate the lens decentration (LD) of orthokeratology (ortho-k) and the association between pretreatment corneal topographic parameters and LD of the ortho-k. Methods: Fifty right eyes of 50 myopes wearing ortho-k lenses were included in the prospective study. Corneal topography was conducted pretreatment to get topographic corneal parameters, including flat-K (K1 ); steep-K (K2 ); corneal astigmatism (CA), CA at 0 to 3 mm (3 mm-CA), 3 to 5 mm (5 mm-CA), 5 to 7 mm (7 mm-CA); surface asymmetry index (SAI); surface regularity index; the curvature of best-fit sphere; the diameter of cornea (DC); the distance from the corneal center to the corneal vertex (CCCV); flat eccentricity (E1 ), steep eccentricity (E2 ), and E1 /E2 (E ratio); and the corneal curvature differences between the nasal and temporal quadrants at 0 to 3 mm (3 mm-Knt ), and the corneal curvature differences between the superior and inferior quadrants at 0 to 3 mm (3 mm-Ksi ), 5 mm-Knt (at 3–5 mm), 5 mm-Ksi (at 3–5 mm), 7 mm-Knt (at 5–7 mm), and 7 mm-Ksi (at 5–7 mm). The relationship between these cornea topographic parameters and LD of the ortho-k was tested using stepwise multiple linear regression models. Results: The mean magnitude of LD was 0.51±0.23 mm (0.06–1.03 mm). According to the stepwise analysis, 4 factors were associated with the overall LD ( P <0.01): SAI (β=0.252), CCCV (β=0.539), 5 mm-CA (β=−0.268), and 3 mm-Ksi (β=−0.374); 5 factors were associated with the horizontal LD ( P <0.01): DC (β=0.205), CCCV (β=0.881), 3 mm-CA (β=−0.217), 5 mm-Knt (β=0.15), and 3 mm-Ksi (β=−0.18); and 3 factors were associated with the vertical LD ( P <0.01): SAI (β=0.542), 5 mm-CA (β=−0.188), and 3 mm-Ksi (β=−0.213). Conclusion: Lens decentration is most common, but in most cases, the amount of LD is moderate and acceptable. The magnitude of LD can be predetermined by topographic corneal parameters. Surface asymmetry index, CCCV, 5 mm-Knt, and 3 mm-Ksi may be more preferable parameters in terms of the assessment of LD of ortho-k.